Brevitentoria Weaver 1984 (Trichoptera: Integripalpia) of Espírito Santo State, Brazil: New records and new species - Neto, Pedro Bonfá; Vilarino, Albane; Salles, Frederico F. (Zootaxa, 2023)
In Brazil, about 900 species of Trichoptera have been recorded, with some species in all Brazilian states. Nevertheless, the collection effort is unequal, with several under-sampled regions. Despite being located entirely within the Atlantic Forest ecoregion, a hotspot of biodiversity, Espírito Santo State has a low known caddisfly richness when compared to nearby areas in the same ecoregion, especially for the infraorder Brevitentoria. This suggests the existence of a Trichoptera biodiversity knowledge gap. Aiming to overcome these taxonomic and distributional shortfalls, we performed a comprehensive inventory of the Brevitentoria species in the state. The sampled sites were distributed from North to South of the state covering 22 locations. In total, 3,420 adult specimens of Brevitentoria were analyzed, leading to a total of 40 species. Two families and 27 species are recorded for the first time from the state. Additionally, we describe three new species of the genera Phylloicus, Helicopsyche (Feropsyche), and Marilia. As a result of this survey, we increase by 100% the number of species of Brevitentoria known from the state, and by 30% for the number of known Trichoptera species. Based on incidence data from this inventory and from the literature, the Brevitentoria species richness was estimated to be about 72 species in Espírito Santo State.